The Influence of Workplace Facilities on Employee Job Satisfaction at the Makassar Metropolitan Police Office (Polrestabes Makassar) - Iriyamayanti; Ramli, Anwar; Haeruddin, M. Ikhwan Maulana; Kurniawan, Agung Widhi; Burhanuddin (Bulletin of Management and Business, 2025)
This study aims to examine the influence of workplace facilities on employee job satisfaction at the Makassar Metropolitan Police Office (Polrestabes Makassar), with a particular focus on the Traffic Unit. A quantitative research design employing a descriptive-associative approach was utilized. The study population comprised 107 employees of the Traffic Unit, from which 85 respondents were selected through random sampling techniques. Data were collected using structured questionnaires and analyzed through simple linear regression with the assistance of SPSS (Statistical Package for the Social Sciences) version 27. The findings reveal that workplace facilities exert a positive and statistically significant influence on employee job satisfaction. This relationship is evidenced by the adequacy of office infrastructure, operational equipment, information technology support, and welfare-related amenities. Nevertheless, certain aspects such as internet accessibility and the comfort of rest areas require further improvement. The study provides valuable insights for Polrestabes Makassar in formulating policies aimed at enhancing workplace facilities and offers a useful reference for future research on job satisfaction within government institutions.